(untitled) (CIPEEX, 2026)
Introduction: Patients with severe COPD present systemic repercussions, including nutritional impairment and hemodynamic alterations. Objective: To evaluate the effects of nutritional status and supplementation with hydrolyzed collagen peptides (25 g/day for 12 weeks) on hemodynamic parameters obtained by PhysioFlow®. Methods: Clinical trial with allocation into a control group (CG) and a supplemented group (SCG). Stroke volume (SV), stroke volume index (SVI), cardiac output (CO), cardiac index (CI), systolic blood pressure (SBP), systemic vascular resistance (SVR), end-diastolic volume (EDV), and early diastolic function rate, among others, were assessed. Statistical analysis was performed using GraphPad Prism, with significance set at p<0.05. Results: An increase in SV (p=0.0092) and CO (p=0.0235) was observed in the SCG compared to the pre-intervention period, along with a reduction in SVR (p=0.0393) and an increase in EDV (p=0.0053). SBP showed a slight reduction in the SCG (p=0.0245). Conclusions: The findings suggest improved pump function and systemic hemodynamics after supplementation with collagen peptides in severe COPD.